Infrastructure scour management: a case study for A68 Galadean Bridge, UK. Issue 1 (19th July 2019) - Koursari, Eftychia; Wallace, Stuart
Abstract : Scour can be responsible for compromising the stability of bridges and, if not identified early and adequately addressed, can lead to the catastrophic failure of a structure. BD 97/12 of the Design Manual for Roads and Bridges is used for the assessment of bridges and other structures over or adjacent to a watercourse and allows application of risk ratings based on variable circumstances and therefore a logical approach to investment in scour-related issues. Structures considered to be particularly at risk of scour are being subject to reactive safety inspections following events likely to increase water levels. This study describes efforts to use engineering measures for increased protection against scouring at A68 240 Galadean Bridge, UK. In this case, sediment transport has formed an island upstream of the structure, introducing a bend into what used to be a straight section of Leader Water, resulting in the river being redirected towards the western riverbank. As a result, the northwestern embankment of the A68, the outer side of the bend, has been significantly eroded. This case study emphasises the importance of changes in the morphology of a watercourse to be identified at early stages.